-9h-1=17

Simple and best practice solution for -9h-1=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9h-1=17 equation:


Simplifying
-9h + -1 = 17

Reorder the terms:
-1 + -9h = 17

Solving
-1 + -9h = 17

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -9h = 17 + 1

Combine like terms: -1 + 1 = 0
0 + -9h = 17 + 1
-9h = 17 + 1

Combine like terms: 17 + 1 = 18
-9h = 18

Divide each side by '-9'.
h = -2

Simplifying
h = -2

See similar equations:

| 8-9x=40 | | 3z-5z=10 | | 2x+7=12-3x | | 6.25+(4-2.5)= | | 4x+7=-2+37 | | (b-1)(b-1)=0 | | 2(7x-3)-9=6x-(2x-5)+10 | | 6x+3=4x+17 | | -5+-2=3t-2 | | 45+10x=105 | | 7x-(2x-2)-8=3(4x-9)+7 | | -3y-1=-2y+2 | | 21a=56+7a | | -2q=-4q-10 | | 23+3(4x-5)=-4-6x | | 17=10h-3h+3 | | x^2-3x-3=0 | | 41+(3x+4)=0 | | 18-5(2x+3)=9-15x | | 10n=36-2n | | -11x+2y=4 | | 4x+8=10x-2(3x-4) | | 17=10h-3+3 | | 17=10-3+3 | | 16h+25h+3h-4=84 | | y=20-3y | | 7=10-3+3 | | 9c^2+6c+1=0 | | 5x+2x-3=18 | | 3x-7=11x-(8x-2) | | 20-w=6w | | 2x-3(4-x)=8+4(x-1) |

Equations solver categories